Comparison of Clinical and Reproductive Outcomes between Adenomyomectomy and Myomectomy - Hlinecka, Kristyna; Mara, Michal; Boudova, Barbora; Lisa, Zdenka; Richtarova, Adela; Kuzel, David (Journal of minimally invasive gynecology, 2022)
STUDY OBJECTIVE: Women with adenomyosis may show a lower pregnancy rate and a higher miscarriage rate than healthy women. There is also a general agreement that leiomyomas, either submucosal or intramural, negatively affect fertility, when compared with women without myomas. Some of these women may benefit from adenomyomectomy, however this cytoreductive procedure is considered invasive and technically challenging especially in severe diffuse cases. The study aimed to compare the clinical and reproductive outcomes of patients who underwent adenomyomectomy with those of patients who underwent intramural myomectomy. DESIGN: A retrospective study. SETTING: Department of Obstetrics & Gynecology, Center of Gynecological Endoscopy and Minimally Invasive surgery, First Faculty of Medicine, General University Hospital in Prague. PATIENTS: A total of 55 women who underwent surgical resection of uterine adenomyosis and 55 patients who underwent myomectomy for intramural uterine myomas were included in this study. All study participants wished to retain and possibly improve their reproductive potential. INTERVENTIONS: Between 2004 and 2019, 110 women underwent laparoscopic or open uterus-sparing surgery for clinically significant uterine adenomyosis (group A) or myomas (group B), respectively. MEASUREMENTS AND MAIN RESULTS: Two groups of women who underwent different fertility-saving procedures were compared. Although all women entering the study had declared their wish to conceive, only 28 patients in group A (group A1) and 24 women in group B (group B1) finally aimed toward pregnancy. The mean age and follow-up period was 35.0 years and 76.81 months, respectively, in group A and 34.8 years and 72.5 months, respectively, in group B. The pregnancy and delivery rates were 75.0% and 46.4%, respectively, in group A1 vs 96.0% and 70.8%, respectively, in group B1, with no significant differences between the 2 groups. The open surgical approach was significantly more frequently employed in group A (47.3% vs 16.4%; p <.01). CONCLUSION: In this study, women who underwent surgery involving the uterine muscularity, including myomectomy or adenomyomectomy, had comparable reproductive outcomes, with no significant differences.
Keywords: leiomyom; Uterine Myomectomy; Retrospective Studies; těhotenství; Uterine Neoplasms; výsledek terapie; Leiomyoma; Myoma; Laparoscopy; Adenomyosis; ženské pohlaví; nádory dělohy; retrospektivní studie; Humans; Pregnancy; Fertility outcome; myomektomie; Fertility saving procedure; adenomyóza; Female; laparoskopie; Treatment Outcome; lidé